2023
DOI: 10.3389/fpsyt.2023.1108902
|View full text |Cite
|
Sign up to set email alerts
|

Frailty is associated with worse cognitive functioning in older adults

Abstract: IntroductionFrailty and impaired cognitive functioning often co-occur in older adults and are associated with adverse health outcomes. However, their relationship is unclear. This study sought to examine the association of frailty status with cognitive functioning in older adults.MethodThe study population consisted of 2,296 older adults aged ≥60 from the National Health and Nutrition Examination Survey 2011–2014. Frailty status was measured based on the Fried Phenotype and the participants were categorized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…In the present study, we categorized participants' plasma levels of lead into four groups based on quartile and used the 1st quartile (the lowest quartile) as a reference. This is consistent with prior NHANES-based epidemiological studies (Fu et al, 2022a,b;Li et al, 2023).…”
Section: Methodssupporting
confidence: 93%
“…In the present study, we categorized participants' plasma levels of lead into four groups based on quartile and used the 1st quartile (the lowest quartile) as a reference. This is consistent with prior NHANES-based epidemiological studies (Fu et al, 2022a,b;Li et al, 2023).…”
Section: Methodssupporting
confidence: 93%
“…This alarming gure highlights that frailty requires greater attention and researchers need to elucidate the mechanisms of frailty to be able to reduce the risk of dementia (26). In our cohort, frailty had a poorer outcome on global cognition and attention and Li et al (27) similarly found that frailty is associated with worse global cognition, processing speed, attention and working memory. Additionally, frailty was associated with poorer executive function performance which was also similarly found by Gross et al (28) where they established that the hazard ratio of frailty was associated with quicker deterioration on the TMT B task.…”
Section: Discussionsupporting
confidence: 62%
“…38 Unemployment is associated with more risk of decreased income, lack of household income, loss of health insurance, and inability to collect valuables assets. 30 Unemployment is closely related to the poverty rate, and poverty is a well-known socioeconomic determinant related to health. 39 A longitudinal study conducted in Taiwan from 1999 to 2007 found that late-career unemployment significantly increased the risk of frailty in later life.…”
Section: Discussionmentioning
confidence: 99%